Backwards And Forwards - Hickling, R.H. (Journal of Malaysian and Comparative Law, 2002)
One day in the nineteen-fifties I was seated at a long table in the Chief Secretary's Office in the old Secretariat, Kuching - now, I believe, the Chief Judge's Chambers. The Governor was presiding over the weekly meeting of the Supreme Council, and I was attending as acting Attorney-General.